2009
DOI: 10.1021/la901481q
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Assisted Dewetting during Chemical Vapor Deposition

Abstract: This study examines the use of a nonreactive solvent vapor, tert-butanol, during initiated chemical vapor deposition (iCVD) to promote polymer film dewetting. iCVD is a solventless technique to grow polymer thin films directly from gas phase feeds. Using a custom-built axisymmetric hot-zone reactor, smooth poly(methyl methacrylate) films are grown from methyl methacrylate (MMA) and tert-butyl peroxide (TBPO). When solvent vapor is used, nonequilibrium dewetted structures comprising of randomly distributed poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…However, the formation of a rough surface suggests that either some porogen is present in the film, leading to growth of concentration fluctuations, or dewetting of deposited PGMA from the underlying layers occurs and persisting throughout the film. In our prior studies, we observed similar autophobic dewetting of poly(methyl methacrylate) films when iCVD was conducted on silicon surfaces . Figure b–d also shows that, when both the porogen and monomer's degree of saturation exceed unity ( P m / P m‐sat >1, P p / P p‐sat >1), porous polymer films can be grown.…”
Section: Resultssupporting
confidence: 63%
“…However, the formation of a rough surface suggests that either some porogen is present in the film, leading to growth of concentration fluctuations, or dewetting of deposited PGMA from the underlying layers occurs and persisting throughout the film. In our prior studies, we observed similar autophobic dewetting of poly(methyl methacrylate) films when iCVD was conducted on silicon surfaces . Figure b–d also shows that, when both the porogen and monomer's degree of saturation exceed unity ( P m / P m‐sat >1, P p / P p‐sat >1), porous polymer films can be grown.…”
Section: Resultssupporting
confidence: 63%
“…There, film growth is limited by monomer adsorption onto a growing polymer film. 12,13 Experiments conducted at or beyond monomer saturation (P m / P sat > 1) showed significantly higher deposition rates, and the deposition rate increased nearly linearly with P m /P sat . The maximum deposition rate observed was about 600 nm/min (P m /P sat = 2.18).…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, fast deposition can suppress thin-film dewetting, leading to smaller droplets with greater surface area. 12 Similarly, small molecule crystal nucleation and growth can be modulated by deposition rate. 13,14 The relatively high capital cost of vacuum process equipment is a major obstacle to widespread iCVD commercialization.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is well-known that the autophobic dewetting of some liquids is caused by the formation of an adsorbed monolayer of the liquid at the liquid-solid interface [25]. Different factors are responsible for such autophobic behavior during solvent-assisted deposition, including surface energy properties of liquid films and substrates [25][26][27], type of solvent used and the concentration of the solution [28][29][30], the molecular weight of the liquid and film thickness [31,32], conformational characteristics of liquid molecules and molecular packing of the layer adsorbed at the solid surface [26][27][28]30,33], etc. Different situations can give different types of structures at a solid surface, such as compact monolayers, bilayers and thicker films [34].…”
Section: Introductionmentioning
confidence: 99%